PERBANDINGAN HASI BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DAN TIPE TALKING STICK DI KELAS X AP SMK NEGERI 2 PALU - Mirawati, Ni Wayan; Hasan, Hasan; Nuraedah, Nuraedah (Katalogis, 2018)
Purpose this research is to describe the differences in student learning outcomes given the model of cooperative learning type Make a Match and students who are given cooperative learning model type Talking Stick. This research was conducted in SMK Negeri 2 Palu using experimental method. Cooperative learning model is divided into two factors, the model of cooperative learning type Make a Match and cooperative learning model type Talking Stick. Data analysis used is t-scheffe test analysis with 5% significant level, obtained thitung = -0,084 < ttabel = 2,01, then H0 accepted, The result of research indicate that there is no difference of learning result of student's history given model of Make a Match and the students who are given the Talking Stick model and the learning outcomes of cooperative learning model Talking Stick type is higher than the Make a Match type in the class X AP SMK Negeri 2 Palu.